Prenatal maternal inactivated COVID-19 vaccination: the maternal and neonatal outcomes, a retrospective cohort study - Cai, Yaoyao; Wu, Shenghao; Zhang, Sisi; Xu, Xinxin; Xie, Fengfeng; Gao, Lijun; Xia, Weiting (Frontiers in Pharmacology, 2024)
Background: Despite the widespread adoption of COVID-19 vaccination, a comprehensive understanding of potential vaccine-induced adverse effects, particularly in the context of pregnancy, remains a critical area of investigation. Elevated concerns surround the maternal and neonatal outcomes subsequent to prenatal maternal COVID-19 vaccination. While existing studies have provided insights into the safety profile of COVID-19 mRNA vaccines, the extrapolation of these conclusions to inactivated COVID-19 vaccines poses uncertainties. Notably, limited data are available regarding the maternal and neonatal effects associated with inactivated COVID-19 vaccines. Objective: To evaluate the prenatal maternal inactivated COVID-19 vaccination and the impact on maternal and neonatal outcomes. Methods: This was a retrospective cohort study of women who delivered between January and June 2022 at a single university-affiliated hospital. Those who have completed at least one dose of inactivated vaccine before or during pregnancy were included in “vaccinated group,” and those who were not vaccinated were included in “unvaccinated group,” the maternal, pregnancy and neonatal outcomes were evaluated. Propensity score matching (PSM) was performed to balance the baseline parameters of the two groups. Results: A total of 1926 women were enrolled in this study, 827 (42.94%) women were prenatally vaccinated, and 1099 (57.06%) unvaccinated. The gestational week of delivery were slightly lower in the vaccinated group, 38.61 ± 1.89 weeks in the vaccinated group and 38.93 ± 1.49 weeks in the unvaccinated group. There was a higher rate of overall preterm delivery in the vaccinated group (aOR 1.61, 95% CI 1.07–2.42; p = 0.02), however, the probability of delivery before 34 weeks and before 32 weeks (early preterm delivery) were similar (p > 0.05). A total of 2009 infants were born, 851 in the vaccinated group and 1158 in the unvaccinated group. There were similar neonatal outcomes in the two groups. Conclusion: Although we found a slightly lower gestational week of delivery and a possible increased rate of late preterm birth in the vaccination group, there was no difference in mean neonatal weight, incidence of low birth weight infants and other neonatal adverse complications. Meanwhile, there was no difference in pregnancy and maternal outcomes between the two groups.